2019
DOI: 10.1167/iovs.18-25924
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological and Psychophysical Studies of Meridional Anisotropies in Children With and Without Astigmatism

Abstract: PURPOSE. We investigated the pattern of meridional anisotropies, if any, for pattern onsetoffset visual evoked potential (POVEPs) responses and psychophysical grating acuity (GA) in children with normal letter visual acuity (20/20 or better). METHODS.A total of 29 children (aged 3-9 years), nine of whom were astigmatic (AS), were recruited. Orientation-specific monocular POVEPs were recorded in response to sinewave grating stimuli oriented along the subjects' principal AS meridians. Horizontal and vertical gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 58 publications
1
26
0
Order By: Relevance
“…Up until approximately school age, childhood astigmatism can potentially affect normal visual development and is associated with amblyopia, abnormal binocular vision and myopia development . Some authors recommend that astigmatism as low as 0.50 D should be corrected, particularly if associated with oblique or against‐the‐rule (ATR) axes, or if asthenopic symptoms are present aligning with findings from a recent study that reported a trend of better grating acuity (and visually evoked potential amplitude) in children without astigmatism, compared to those with astigmatism as low as 0.50 DC (who were corrected) . Other authors suggest that astigmatism of 0.75 D or more should always be corrected in school children, irrespective of symptoms .…”
Section: Vision Refractive Error and Academic Performancementioning
confidence: 76%
“…Up until approximately school age, childhood astigmatism can potentially affect normal visual development and is associated with amblyopia, abnormal binocular vision and myopia development . Some authors recommend that astigmatism as low as 0.50 D should be corrected, particularly if associated with oblique or against‐the‐rule (ATR) axes, or if asthenopic symptoms are present aligning with findings from a recent study that reported a trend of better grating acuity (and visually evoked potential amplitude) in children without astigmatism, compared to those with astigmatism as low as 0.50 DC (who were corrected) . Other authors suggest that astigmatism of 0.75 D or more should always be corrected in school children, irrespective of symptoms .…”
Section: Vision Refractive Error and Academic Performancementioning
confidence: 76%
“…43,44 The oblique effect can be defined as more sensitive cardinal meridians compared with the oblique meridians, which is normally observed in adults; whereas the horizontal effect is defined by less sensitive horizontal meridians compared with the vertical and oblique meridians. Our previous study in children with normal vision found a horizontal effect, 41 where electrophysiological signals in response to binocular stimulation using horizontal gratings of 4 cpd were significantly poorer than the vertical and oblique gratings. This type of meridional anisotropy has been postulated to be an adaptative strategy for the visual system to optimize the perception of orientations that are less naturally encountered.…”
mentioning
confidence: 75%
“…Their visual processing in response to orientation-specific grating stimuli was evaluated using electrophysiological and psychophysical techniques, as published previously for non-amblyopic children. 41 The research study adhered to the tenets of Helsinki and ethical approval was obtained from the Centralized Institutional Review Board (CIRB) (Registration number: R1083/98/2013) at SingHealth and ratified by the human research ethics committees at the University of New South Wales, Sydney, New South Wales, Australia (Approval number: 09364). Parents and guardians gave their informed consent and children six years of age and above provided assent.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations